The family novels. Intergenerational novels, family memoirs, changing society in changing in changing fiction forms. New approaches to the family Novel in European and American literature from 1950 to 2010 - (:unkn) unknown (My University, 2025)
The aim of this project is to investigate the formal characteristics and the main developments of the family novel from 1950 to 2010 in European and American literature. With family novel we mean the typology of novel that proposes the narration of the history of a real or fictional family and is focused on the intra- and inter-generational interpersonal relationships, the identifying heritage connected to the family roots and the ways of dialogue in the domestic space that favours the formation of a specific family and civic lexicon. The background hypothesis of the research is that it is possible to distinguish the family novel from other forms of novel not only on the basis of its content (the history of a family) but also on the basis of its form (internal structure, point of view from which the history is narrated, functions of the characters). Particular attention will be paid in this sense to family memoirs, hybrid forms that lie in a significant area on the border of novel, récit d’enfance and autobiography. To date, both studies dedicated to the family novel and to different forms of autobiography, have omitted a study dedicated to theorising this specific form. The research aims, first of all, at filling this gap. The crisis of the patriarchal family, the emancipation of the woman, the advent of new one-parent families and homo-parental families has produced a profound change of family models of reference. The second starting hypothesis of this research is that the deep structural changes that the family has seen in the last few decades also had an impact on the way in which families are imagined and represented in literature: new forms of fiction are elaborated, in which to narrate family history. We aims thus to provide a new definition of the family novel and a new theoretical model for the study of family novels from the last 60 years, by focusing its attention on some specific topics: Great-History and micro-stories; the historical sources (memory and archives); the dinner scene and the argumentative strategies of the family at mealtime; the representation of post-bourgeois families in post-modernist forms; family novel and ethnic minorities (Jewish family novel and migrant writers). The project will use research methods belonging to literary criticism and to comparative literature. For a necessary dialogue between consolidated research practices and innovative approaches we aim to combine a historical-literary analysis with the study of the morphology and genres, and the traditional methods of close reading with the most recent challenges offered by the wider horizon of distant reading. However, in an interdisciplinary view, and according to the competences of the different team members, we will consider also some specific investigation tools that other humanities adopt in the study of the family, and we will try to test their applicability to the study of the representations of the family in literature. In this sense, a new impulse to the study of the family novel comes from the recent publication of Family Politics (Ginsborg 2013) which confirms how choosing the family situation and its representations as a research tool can offer an innovative approach to the study of the contemporary period and a new challenge for the humanities. The PI will collaborate with a team of researchers from different disciplines: comparative and Italian literature, psychology, and sociology of literature. Besides a wide range of competences, the research group can count on the presence of researchers with different experience – from senior members to PhD students - and from three universities - Napoli Federico II, Paris Ouest Nanterre and Neuchâtel. The initial research team will be enriched by an additional team made up of two post-doc researchers (preferably one in the literary field and one in the historical field).
Keywords: family memoirs; discourses; novels